Serum Ace and Ace I/D Polymorphism: Risk of Type 2 Diabetes with and Without Nephropathy in Pakistani Cohort - Hiba Bano; Mehir un Nisa Iqbal; Nazish Iqbal Khan; Taseer Ahmed Khan (KARACHI MEDICAL AND DENTAL COLLEGE, 2022)
Objective: To find serum ACE (Angiotensin converting enzyme) level and the role of ACE I/D polymorphism with T2DM (Type 2 Diabetes Mellitus) among the Pakistani cohort. Methods: A total of 110 diagnosed T2DM patients and 100 normotensive healthy controls with an age range of 35-65 years were randomly selected for this study. All cases were screened for the T2DM based on random and fasting blood sugar levels and confirmed by HbA1c test. Genomic DNA was extracted from peripheral blood samples by the Salting out method and ACE I/D polymorphism was genotyped using insertion-deletion polymorphism. A serum level of ACE was also determined. All statistical analysis was conducted using SPSS 16 and all values are significant at a p-value less than 0.05. Hardy Weinberg Equilibrium (HWE) was calculated for any deviation of allele frequencies from predicted. The Chi-square test was used to evaluate the association between ACE polymorphism and the risk of diabetes. The odds ratio along with a 95% confidence interval via binary logistics regression analysis was used to find out the diabetic risk associated with ACE genotyping. Results: The analysis showed higher ACE levels among T2DM patients with nephropathy (mean =158 ± 38.9) and without nephropathy (mean = 128.23 ± 46.8) as compared to controls (mean = 94.4± 28.6). No significant association (÷2 = 7.402, p-value=0.116) was observed between ACE genotyping and T2DM. However, those who have DD (O.R= 2.714, 95% CI=0.943-7.809) genotype of ACE polymorphism was at risk of diabetes but the results were non-significant. However, no risk was present at the diabetic nephropathy females. Conclusion: These outcomes propose that the ACE gene may not contribute to T2DM in the Pakistani cohort. However, ACE levels were higher among T2DM with and without nephropathy patients.